Geological Aspect of Slope Failure and Mitigation Approach in Bireun - Takengon Main Road, Aceh Province, Indonesia - Ibnu Rusydy; Didik Sugiyanto; Lono Satrio; . Zulfahriza; Imam Munandar (Aceh International Journal of Science and Technology)
A soil and rock slope assessment survey was conducted along Bireun – Takengon main road in Aceh Province, Indonesia. The slope assessment survey was carried out to determine the geological condition, verify and identify the potential areas of slope failure and to study what type of slope stability and protection method could be applied to the road. Several research methodologies were conducted in the field such as rock and soil identification, and slope assessment. The survey was conducted in four selected areas along Bireun – Takengon main road. In study area I, soil creep occurred because of a presence of montmorillonite clay. The mitigation methods to reduce soil creeping in this area are building a retaining wall and pile. The shotcrete, wire mesh, net rock bolting, and rock removal method is suitable to apply in study area II. The shotcrete and soil nails were used because the type of rocks in those areas is sedimentary rock such as shale, sandstone, siltstone, and a boulder of a volcanic rock. The same approach shall be applied in study area IV. study area III was the best spot to learn about the mitigation approach for slope stability and provides many lessons learned. Aceh Province experience active tectonic movement, high intensity of rain, geological structures, a high degree of weathering, and high intensity of earthquake,as primary factors which trigger landslides. The techonology of slope stabilizing and protection methods can be applied to mitigate landslides.